Complete Genome Sequence of Bacteroides ovatus V975 - Wegmann, Udo (Genome Announc, 2016)
The complete genome sequence of Bacteroides ovatus V975 was determined. The genome consists of a single circular chromosome of 6,475,296 bp containing five rRNA operons, 68 tRNA genes, and 4,959 coding genes.